Fator stress: o trabalho como sofrimento psíquico nas organizações - Freire, Roberta da Silva (2014)
The present study aims to identify and describe the main stressor agents from the Occupational Stress, its consequences for the subject, relating it to the types of work organizations. To this end, this study was conducted by means of bibliographical and field researches, with face-to-face interviews been carried out previously, structured with fifteen Psychology professionals working in the clinical area in order to check the number of subjects with Occupational Stress complains related to pathogenic psychological distress. Data were analyzed by the method of content analysis of qualitative approach. The results showed the identification of stressor agents from the Occupational stress and its consequences for the subject, through the mapping of symptoms and diseases, and also, the presence of this kind of stress in different types of work organizations , promoting the pathogenic psychological distress in subjects, changing its relationship with the work.